Multiple cranial neuropathies following zoledronic acid infusion: a relationship? Clinical features and pathogenic discussion concerning a case. Issue 8 (August 2016) - Deshayes, S.; Martin Silva, N.; Cogez, J.; Baldolli, A.; Fedrizzi, S.; Bienvenu, B.; Aouba, A.
Abstract The widespread use of bisphosphonates, especially in osteoporosis, has led to a greater number of reports of side effects. We describe for the first time a case of a 75-year-old female patient with a history of indolent sicca syndrome who developed multiple cranial neuropathies after zoledronic acid infusion. In this case, the elimination of the main causes of multiple cranial neuropathies, the chronology with zoledronic acid infusion, the absence of secondary complications of the Sjögren's syndrome, reported cases of similar peripheral nerve injuries with interferon infusions, the spontaneous remission of this multiple cranial neuropathy in parallel with the induced flu-like syndrome, argue for its iatrogenic origin, probably by a great release of inflammatory mediators in this particular background of primary Sjögren's syndrome.